Analysis of Characteristics and Storage Time of Multimaterial and Monomaterial Snack Packaging: Analysis of the Characteristics and Shelf Life of Multimaterial and Monomaterial Snack Packaging - Addinda Revi Liana (P3M Politeknik Negeri Media Kreatif, 2025)
The increasing volume of flexible packaging waste in Indonesia drives the need for environmentally friendly packaging solutions. This study compares the physical, mechanical, and stability characteristics of monomaterial and multimaterial snack packaging, each with a net weight of 68 grams. Conducted at PT. X, the research uses a quantitative comparative approach. Two packaging structures were tested: OPP/ink/PE/VMBOPP/Resin PP (monomaterial) and OPP/ink/PE/VMPET/CPP (multimaterial). Parameters tested include WVTR, O₂TR, tensile strength, sealing strength, bonding strength, and COF. Samples were conditioned in an oven at 80°C for 7 weeks to simulate three years of room temperature storage. Results show that monomaterial packaging performs competitively, particularly in WVTR and tensile strength, although its O₂TR is higher. Its recyclability highlights significant potential in supporting plastic waste reduction policies and contributes to the development of sustainable packaging in the snack food industry.